Teknik Permainan Saxofon Alto Oleh Jetro Manalu Dalam Mengiringi Repertoar: Studi Kasus Upacara Pernikahan di Sidikalang - Algoboy N. Nainggolan; Hendrik L. Simanjuntak; Kamaluddin Galingging (Visi Sosial Humaniora, 2026)
This study aims to examine Jetro Manalu's alto saxophone playing technique and analyze its application in performing repertoire at traditional Batak Toba wedding ceremonies in Sidikalang. This study uses a qualitative approach with data collection methods through observation, interviews, and documentation. The research results show that before performing music, Jetro Manalu focuses on two main aspects: instrumentation and instrumentalist. Instrumentation includes warm-up exercises, long tones, scales, and mouthpiece, reed, and tuning checks to achieve optimal and clear sound quality. Meanwhile, the instrumental aspect is related to mastery of tempo, dynamics, and expression in playing. In addition, this study found a process of adapting the sulim voicing technique in the Toba Batak music tradition into saxophone playing, especially when performing the Gondang Si Bunga Ri repertoire. The adaptations include three main techniques: mangarutu, mandila-dilai, and manganak-anaki. These three techniques contribute to shaping the gondang melody, enriching its musical articulation, and providing a saxophone sound that reflects the regional nuances of the Toba Batak.